Effect of Aluminum Oxide Powder and Nanoparticles on Kaolinite Mobilization in Sand - Naomi Ogolo; Tessy Achor; Mike Onyekonwu (Computational Engineering and Physical Modeling, 2022)
Al2O3 nanoparticles in sand can militate against mobilization of kaolinite, indicating that Al2O3 powder could also do same but this has not been investigated. In this work therefore, the capacity of Al2O3 powder to militate against clay mobilization in sand is investigated and its performance is compared with the performance of Al2O3 nanoparticles at different water salinity values expressed in mass fraction. Experimental results show that the presence of Al2O3 powder and nanoparticles in sand can militate against kaolinite migration during fluid flow, but the performance of the nanoparticles is more effective than the ordinary powder. At a mass fraction range of zero to 0.04, the volume of clean effluent produced were 5 – 20 pore volumes, 5 – 28 pore volumes and 10 – 48 pore volumes for the control case, use of Al2O3 powder and use of Al2O3 nanoparticles respectively. This indicates that significant volumes of kaolinite free effluents can be produced from sand packs containing Al2O3 nanoparticles than with Al2O3 powder and when Al2O3 is completely absent in sands. It is also observed that produced volumes of clean effluent increases as water salinity increases, implying that kaolinite is prone to mobilization at lower water salinity levels. Linear equations derived from the experimental results and expressed in dimensionless parameters are also presented.